Construction of an eukaryotic expression vector containing IBDV VP2/4/3 and ChIL-2 fusion gene and their expression in Vero cells - WAN Wang-jun; XIE Rong-hui; LI Long; XU Jian; YU Lian (浙江大学学报. 农业与生命科学版, 2005)
Recombinant eukaryotic expression vectors containing fusion genes of infectious bursal disease virus (IBDV) polyprotein (VP2/4/3) gene and chicken interleukin 2 (ChIL-2) gene were constructed using the technique of splicing by overlapping extension (SOEing) and three times PCR. Fusion gene fragments were directly cloned into pCI, an eukaryotic expression vector, to produce recombinant expression plasmids pCI-VP2/4/3-IL-2 and pCI-IL-2-VP2/4/3. The recombinant plasmids were transfered into Vero cells introduced by Lipofectamine2000 reagent. Gene specific RT-PCR showed that the fusion genes were successfully transcribed in Vero cells. The fusion proteins were detected by indirect immunofluorescence and western-blot assays. These results suggest that the fusion genes were expressed correctly in Vero cells, thus providing a basis for immune-enhancement of ChIL-2 in DNA vaccination against IBDV.